2020
DOI: 10.3390/rel11090478
|View full text |Cite
|
Sign up to set email alerts
|

The Science of Cathedral Studies: Exploring Demographic Profile, Motivational Intentions, and Perceived Impact among those Attending the Holly Bough Service in Liverpool Cathedral

Abstract: The Holly Bough service is a unique pre-Christmas event, combining musical excellence and theological depth, crafted by the founding dean of Liverpool Cathedral in the early twentieth century for the Fourth Sunday of Advent. Located within the developing science of cathedral studies, this paper analyses the demographic profile, motivational intention (drawing on religious orientation theory) and perceived impact on spiritual wellbeing (drawing on Fisher’s four dimensional model) among 564 participants who comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…The 'events' best researched within the science of cathedral studies are the pre-Christmas carol services as evidenced by Walker (2012aWalker ( , 2012bWalker ( , 2013Walker ( , 2015aWalker ( , 2015b. Within the group of studies concerned with carol services, Francis et al (2020b) found that over half of the participants at a pre-Christmas service in Liverpool Cathedral reported that the service had enhanced their sense of well-being over the four domains embraced by Fisher's (1998Fisher's ( , 2016 model of spiritual health. From our analysis of this study, we concluded that the research design was weak, in the sense that it relied on the participants' feeling that the service had acted as an agent of psychological health and well-being for them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The 'events' best researched within the science of cathedral studies are the pre-Christmas carol services as evidenced by Walker (2012aWalker ( , 2012bWalker ( , 2013Walker ( , 2015aWalker ( , 2015b. Within the group of studies concerned with carol services, Francis et al (2020b) found that over half of the participants at a pre-Christmas service in Liverpool Cathedral reported that the service had enhanced their sense of well-being over the four domains embraced by Fisher's (1998Fisher's ( , 2016 model of spiritual health. From our analysis of this study, we concluded that the research design was weak, in the sense that it relied on the participants' feeling that the service had acted as an agent of psychological health and well-being for them.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside the Sunday congregation and the hidden congregation, cathedrals attract different styles of congregations for special events and for special occasions. Amongst these special events and special occasions, the specific event that has received most attention is the Christmas carol service, from both qualitative (Coleman, Bowman & Sepp 2019;Murphy 2016;Muskett 2017;Phillips 2010) and quantitative perspectives (Francis et al 2020b;Francis, Edwards & ap Siôn in press;Walker 2012aWalker , 2012bWalker , 2013Walker , 2015aWalker , 2015b. A particular feature of these studies is that they draw attention to the distinctive profile of the individuals who come to these services.…”
Section: Psychological Health and Well-being Of Participants At Special Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…Testing his model concerning the four ways of belonging to God through the Church of England, Walker focused on two kinds of events: harvest festivals within the rural church (Walker 2009(Walker , 2010a(Walker , 2010b and cathedral carol services (Walker 2012a(Walker , 2012b(Walker , 2013(Walker , 2015. Other researchers, too, working independently over the past decade, drawing on either qualitative or quantitative methods, have identified the importance of carol services within both cathedrals and greater churches for forging contact with a wider range of people than those who would sign up for the kind of membership that entailed a weekly activity (Phillips 2010;Murphy 2016;Muskett 2017;Coleman et al 2019;Francis et al 2020aFrancis et al , 2020bFrancis et al , 2020c. Taken together, these diverse studies begin to provide a rich picture of who attends carol services in cathedrals and greater churches, and why they attend.…”
Section: Carol Services As An Eventmentioning
confidence: 99%